Classification of the Source Base of the Research on Girls’ Labour Training - Slyusarenko, Nina (Pedagogical Discourse, 2013)
The article presents the author’s classification of the source base of the research on girls’ labour training, namely: the works on the formation and development of scientific educational thought and education in Ukraine and its regions; the works on the history of girls’ education and gender issues; the works on the problems of formation and development of pupils’ labour training in Ukrainian schools in the late XIX – XX centuries; the works highlighting the heritage of outstanding educators whose activities were directed towards the effective organization of labour training of the younger generation; the works, the object of research of which is to study the pupils’ labour training at secondary schools abroad; the works dedicated to the problems of labour teacher’s preparation to professional work in higher educational institutions of Ukraine; the results of the investigations of the problems of labour training and education of boys and girls in modern schools of Ukraine.